Evaluation of historical bridges through recreation of GPR models with the FDTD algorithm. (January 2016) - Solla, M.; Asorey-Cacheda, R.; Núñez-Nieto, X.; Conde-Carnero, B.
Abstract: This work presents the evaluation of a medieval masonry bridge that has suffered different restorations throughout history. Ground penetrating radar was used to define the internal state of the structure. Given that the heterogeneity in masonry complicates the interpretation of field data, numerical modelling was employed to improve such interpretation. The combination of photogrammetric and thermographic data, jointly with the development of custom algorithms, was used to create the synthetic model; while real GPR data supported the media characterization. The resulting data allowed for the interpretation of both composition and distribution of different materials in the interior of the bridge. Abstract : Highlights: Evaluation of heterogeneous masonry structures such as restored historical bridges. Comparison of real and synthetic GPR data to identify materials in masonry. Strategies of integrated modelling strategies for the simulation of the GPR signal. Model built from the combination of photogrammetric and thermographic data. The use of Pareto on/off distributions to randomly generate layering.